Effect of tumor microenvironment on ferroptosis: inhibition or promotion - Xia, Zhengzhen; Quan, Yi (Frontiers in Oncology, 2023)
Ferroptosis is a type of lipid peroxidation-induced, iron-dependent programmed cell death. Emerging evidence suggests that ferroptosis is intimately connected to tumorigenesis, development, treatment and plays a major role in tumor immune regulation. This study focused on the connection between ferroptosis and immune regulation, which may offer a theoretical basis for targeting ferroptosis and tumor immunotherapy.